2009
DOI: 10.1073/pnas.0902132106
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor suppresses intestinal carcinogenesis in Apc Min /+ mice with natural ligands

Abstract: Intestinal cancer is one of the most common human cancers. Aberrant activation of the canonical Wnt signaling cascade, for example, caused by adenomatous polyposis coli (APC) gene mutations, leads to increased stabilization and accumulation of ␤-catenin, resulting in initiation of intestinal carcinogenesis. The aryl hydrocarbon receptor (AhR) has dual roles in regulating intracellular protein levels both as a ligand-activated transcription factor and as a ligand-dependent E3 ubiquitin ligase. Here, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
200
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(214 citation statements)
references
References 34 publications
10
200
3
1
Order By: Relevance
“…12,13 In addition to its transcriptional roles, it mediates degradation of proteins through the ubiquitin ligase complex. 14,15 Several endogenous chemicals, including IS, bind to and activate the AHR. 12,16 Therefore, we hypothesized that IS accumulation in CKD patients induces TF through an AHR pathway, thus potentiating thrombosis.…”
mentioning
confidence: 99%
“…12,13 In addition to its transcriptional roles, it mediates degradation of proteins through the ubiquitin ligase complex. 14,15 Several endogenous chemicals, including IS, bind to and activate the AHR. 12,16 Therefore, we hypothesized that IS accumulation in CKD patients induces TF through an AHR pathway, thus potentiating thrombosis.…”
mentioning
confidence: 99%
“…In contrast, compounds 12-14 induced cell death at 10 3 μM ( Figure 5). Moreover, nepitrin (15) and homoplantagenin (16), which are flavone glucosides, showed marked AhR-binding activity at concentrations ranging from 10-10 3 μM lower than those required for binding by indole 3-acetic acid (IAA), a typical natural AhR ligand [8].…”
Section: Identification and Ahr Activity Of Constituentsmentioning
confidence: 99%
“…1-10). , were purified by preparative TLC to afford eight compounds: chryso-obtusin (1), obtusifolin (2), obtusin (3), aurantioobtusin (4), obtusin 2-O-glucoside (5), aurantio-obtusin 6-O-glucoside (6), nor-rubrofusarin 6-Oglucoside (7), and 6-hydroxymusizin 8-O-glucoside (8). Among these isolates, aurantio-obtusin (4) elicited marked AhR activation, followed by obtusifolin (2) and obtusin (3).…”
Section: Identification and Ahr Activity Of Constituentsmentioning
confidence: 99%
See 1 more Smart Citation
“…AHR functions as a ligand-dependent E3 ubiquitin ligase of certain nuclear receptors (Ohtake et al 2007). Kawajiri et al (2009) reported that AHR played a critical role in the suppression of intestinal carcinogenesis by a previously undescribed ligand-dependent mechanism of proteasomal b-catenin degradation and the natural AHR ligands of indole derivatives such as indole-3-carbinol and 3,3-diindolylmethane suppressed intestinal carcinogenesis in an AHR-dependent manner. More recently, there have been some reports that AHR plays an important role in the modulation of the intestinal immune system (Hooper 2011).…”
Section: Introductionmentioning
confidence: 99%